2018
DOI: 10.1097/md.0000000000011365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functionally-narrowest portion of the pediatric upper airway in sedated children

Abstract: The narrowest portions of the pediatric larynx are the glottis and subglottic region. However, the pliable and paralyzed subglottic region, acting like a curtain, is no resistance when passing an endotracheal tube. Therefore, the ‘functionally’ portion of the pediatric upper airway, which may be the most vulnerable to damage during intubation, is the unyielding portion below the cricoid cartilage. We investigated the functionally-narrowest portion below the cricoid cartilage.Computed tomography (CT) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Since there is evidence that the subglottic transverse diameter is less than the anterior to posterior (A-P) diameter 16,17 , we measured the subglottic transverse diameter, which we believed to be the narrowest part of the child's airway and consistent with other studies [6][7][8][9] . The correlations between the subglottic diameter and outer diameter of ETT in our study were moderate whereas other studies recruiting children aged ≤ 6 years found a strong correlation between the subglottic diameter and outer diameter 6,8,18 .…”
Section: Resultssupporting
confidence: 78%
“…Since there is evidence that the subglottic transverse diameter is less than the anterior to posterior (A-P) diameter 16,17 , we measured the subglottic transverse diameter, which we believed to be the narrowest part of the child's airway and consistent with other studies [6][7][8][9] . The correlations between the subglottic diameter and outer diameter of ETT in our study were moderate whereas other studies recruiting children aged ≤ 6 years found a strong correlation between the subglottic diameter and outer diameter 6,8,18 .…”
Section: Resultssupporting
confidence: 78%
“…Diabetic retinopathy (DR) is one of the most feared complications of diabetes. Several researches have been done to estimate the prevalence of DR (6)(7)(8)(9). Blindness caused by DM currently affects approximately 15 Introduction Larynx is an air passage, phonation organ and acting as a sphincter.…”
Section: Introductionmentioning
confidence: 99%
“…Since the morphometric properties of the larynx alter significantly in childhood period of the life, recent studies focused on properties of pediatric larynx. (6)(7)(8). These studies described the narrowest parts of the pediatric larynx helping the surgeons during surgical procedures such as endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%